2011
DOI: 10.2478/s11756-011-0039-9
|View full text |Cite
|
Sign up to set email alerts
|

Autumn migration of robins (Erithacus rubecula) in Hungary

Abstract: The purpose of this study was to describe the autumn migration dynamics of juvenile (n = 3075) and adult (n = 596) robin Erithacus rubecula in Hungary. Capturing and ringing of birds took place at five bird ringing stations of Actio Hungarica between 13 August and 27 October, 2004. The number of captured juvenile and adult individuals rated to one net was the lowest in the reeds of Izsák and the highest in the woody areas of Szalonna, where adults were present at a higher proportion. The migration dynamics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…According to the recoveries of birds ringed in Tömörd and other Hungarian sites, the Hungarian Common Blackbird and Song Thrush populations winter mostly on the Apennine Peninsula (Csörgõ and Gyurácz 2009b,c). The autumn migration dynamics of European Robins in Tömörd and four other Hungarian ringing sites did not differ significantly from each other (Gyimóthy et al 2011). Based on the estimated time of 10% capture, it may be concluded that juvenile birds started their migration as early as the end of August or the beginning of September, while the migration of adults began later, in mid-September or early October, at the ringing stations in Hungary.…”
Section: Timing Of Migration and Habitat Selectionmentioning
confidence: 78%
“…According to the recoveries of birds ringed in Tömörd and other Hungarian sites, the Hungarian Common Blackbird and Song Thrush populations winter mostly on the Apennine Peninsula (Csörgõ and Gyurácz 2009b,c). The autumn migration dynamics of European Robins in Tömörd and four other Hungarian ringing sites did not differ significantly from each other (Gyimóthy et al 2011). Based on the estimated time of 10% capture, it may be concluded that juvenile birds started their migration as early as the end of August or the beginning of September, while the migration of adults began later, in mid-September or early October, at the ringing stations in Hungary.…”
Section: Timing Of Migration and Habitat Selectionmentioning
confidence: 78%
“…Usually the migratory passerines seem to use wider habitat during stopovers compared to breeding period, behaving as generalists in the habitat selection (Barlein 1983, Vega Rivera et al 2003, Chernetsov 2006gary during autumn migration but the most Robins occurred in stopover sites surrounding forest and bushy areas (Gyimóthy et al 2011a). The abundance -dependent shift of habitat selection was found only in Great tit.…”
Section: Discussionmentioning
confidence: 99%
“…The species is protected in Hungary (BirdLife Hungary 2018). Robin is one of the most common migrants from March to mid-April in spring and from September until mid-November in autumn (Antli & Németh 1998, Hadarics & Zalai 2008, Gyurácz & Csörgő 2009, Gyimóthy et al 2011b). The autumn migration has one wave, the breeding population depart until the middle of September and use south-western and south-eastern ways to the wintering areas (BirdLife Hungary 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the Hungarian breeding birds leave the Carpathian Basin and use south-western (and winters in the Apennine Peninsula and on the surrounding islands) and south-eastern ways to the wintering area by mid-September (BirdLife Hungary 2018). Autumn passage migration peaks in late September to early October in Hungary (Gyurácz et al 2008, Gyimóthy et al 2011b. The stopover duration is 4-9 days on average (Gyimóthy et al 2011b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation